Low self-perception of malnutrition in older hospitalized patients - Lueg, Gero; Wirth, Rainer; Kwiatkowski, Julia; Rösler, Alexander; Jäger, Martin; Gehrke, Ilse; Volkert, Dorothee; Pourhassan, Maryam (Clinical Interventions in Aging, 2020)
Background: Studies focusing on self-perception of nutritional status in older hospitalized patients are lacking. We aimed to examine the self-perception of body weight and nutritional status among older hospitalized patients compared to their actual body weight and nutritional status based on medical assessment. Materials and Methods: This observational cross-sectional study investigated 197 older participants (mean age 82.2±6.8 years, 61% women) who were consecutively admitted to the geriatric acute care ward. Body weight status and nutritional status were assessed using WHO-BMI classification and Mini Nutritional Assessment-Short Form (MNA-SF), respectively. Self-perceived body weight status and nutritional status were assessed with a standardized question-naire. A follow-up was performed with a short telephone interview after three months. Results: According to MNA-SF, 49% and 35% were at risk of malnutrition and malnour-ished, respectively. There was no agreement between self-perceived nutritional status and objective nutritional status according to MNA-SF (Kappa: 0.06). A slight agreement was found between subjective body weight status and objective body weight status according to WHO-BMI classification (Kappa: 0.19). A total of 184 patients completed the 3 months follow-up and additional 9 patients died during this time, of which 7 and 2 were malnourished and at risk of malnutrition according to MNA-SF, respectively. Of those who were malnourished and at risk of malnutrition based on MNA-SF and died during follow-up, 67.7% did not realize their malnutrition. Compared to the patients with normal nutritional status during hospitalization, malnourished patients based on MNA-SF had higher rates of unplanned hospital readmission and further weight loss and more often reported health deterioration and experienced death within three months after discharge. Conclusion: No agreement between self-perceived nutritional status and objective nutritional status among older hospitalized patients was found. Our study highlights the need to raise knowledge about the issue of malnutrition and increase awareness of health risks associated with malnutrition among older hospitalized patients.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Body weight; Geriatrics; Malnutrition; Older patients; Self-perception